Clinicopathological factors associated with the presence of tumor deposits in resected gastric cancer patients - Paredes Torres, O (2021)
Purpose: The role of tumor deposits (TDs) in the staging of gastric cancer is currently debatable. TDs are defined as tumoral nodules in perigastric adipose tissue with no evidence of lymphatic, vascular, or neural structures. Clinicopathological factors related to the presence of TDs are not well defined. This study aimed to identify the clinicopathological factors associated with the presence of TDs in resected gastric cancer patients. Materials and methods: This prospective study included patients diagnosed with gastric cancer and treated with D2 radical gastrectomy from January 2019 to January 2020. Univariate and multivariate analyses were performed to determine the factors related to the presence of TDs. Results: A total of 111 patients were eligible and TDs were present in 31 of them (28%). In the univariate analysis, male gender (p = 0.027), tumor size ≥ 5cm (p = ≤0.001), serosa and adjacent organs invasion (pT4a and pT4b) (p = ≤0.001), ≥16 metastatic lymph nodes (pN3b) (p = ≤0.001), and TNM stage III tumors (p = ≤0.001) were significantly associated with the presence of TDs. The multivariate analysis showed that a tumors size ≥5 cm (OR = 3.69, 95% CI: 1.17-11.6), serosa and adjacent organs invasion (pT4a and pT4b) (OR = 3.78, 95% CI: 1.31-10.86) and ≥16 metastatic lymph nodes (pN3b) (OR = 3.21, 95%CI:1.06-9.7) were independent risk factors for the presence of TDs. Conclusions: Larger tumors (tumor size ≥ 5cm), serosa and adjacent organs invasion (pT4 and pT4b), and ≥16 metastatic lymph nodes (pN3b) were independent risk factors for the presence of TDs. Keywords: Gastric cancer; Pathology; Surgery; Tumor deposits (TDs).